The impact of the digital economy on occupational health: A quasi-experiment based on “Broadband China” pilot - Wang, Fanfan; Wang, Zheng (Frontiers in Public Health, 2023)
The recent years’ booming digital economy can not only benefit businesses, but also be an important way to improve people's well-being. This paper aimed to identify the relationship between the digital economy based on the "Broadband China" pilot policy and occupational health by applying DID method. The empirical results highlight that occupational health in the pilot cities of "Broadband China" are significantly improved compared with those in non-pilot cities, indicating that the digital economy can significantly improve occupational health. However, this effect varies across regions with different levels of economic development. Compared with developed areas, the digital economy has a more obvious effect on the improvement of occupational health in less developed areas, which indicates that this effect conforms to the law of diminishing marginal effect. Therefore, the digital economy should be continuously promoted to improve occupational health. Governments at all levels should strengthen the network infrastructure to provide a good basic environment for the development of the digital economy. At the same time, governments should introduce more detailed digital economy goals and programs according to the actual situation of their jurisdictions to fully release the economic and social benefits of the digital economy.